The Dark Web and anonymizing technologies: legal pitfalls, ethical prospects, and policy directions from radical criminology. - Davis, Shelby; Arrigo, Bruce (Crime, Law & Social Change, 2021)
Although, in recent years, research surrounding the Dark Web has emerged, governments, policymakers, and stakeholders still lack a firm grasp on the extent of the Dark Web's pitfalls and prospects, bringing the development of legal policy and ethical practice in this area to an alarming halt. To worsen matters, with each day that accountability institutions fail to implement sound legislation to combat the negative side effects and to bolster the positive influences of the Dark Web, the further behind society falls in adequately responding to this mysterious culture and underground world. Accordingly, this article intends to preliminarily address three principal matters. First, it offers a cogent assessment of the advantages and disadvantages of the Dark Web and its anonymizing technologies in order to better predict potential consequences derived from its use and/or regulation. Second, it endeavors to better educate government officials on the legal challenges and ethical benefits that follow from this assessment in order to facilitate the administration of justice. Third, it proposes policy directions from a conflict-informed radical criminology sufficient to rethink future Dark Web activity, including its misuses and abuses. To contextualize these matters, however, the article begins with an overview of the Dark Web and its related anonymizing technologies.